2006
DOI: 10.1139/f06-124
|View full text |Cite
|
Sign up to set email alerts
|

Diel vertical migration in the Lake Superior pelagic community. I. Changes in vertical migration of coregonids in response to varying predation risk

Abstract: The distribution of fishes is influenced by a host of physico-chemical and biological variables, including temperature and oxygen, prey abundance, feeding or assimilation rates, and predation risk. We used hydroacoustics and midwater trawls to measure the vertical distribution of pelagic fishes during a series of research cruises on Lake Superior's western arm in 2001 and 2004. Our objective was to assess vertical structuring in the fish assemblage over varying light levels. We observed variability in vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 27 publications
2
134
0
Order By: Relevance
“…2c), like that of Lake Superior, inhabited deeper water than the lean, and was fatter than the lean as evidenced by its lower percentage buoyancy. The high fat levels in Lake Superior siscowets are hypothesized to be an adaptation for reducing the energetic cost of extensive vertical migration (Henderson and Anderson 2002;Hrabik et al 2006;Jensen et al 2006). A siscowet-like, fat (low percent buoyancy) lake charr was not observed by the author during field surveys of the McTavish (northeast) arm of Great Bear Lake during 2004.…”
Section: Background On Formsmentioning
confidence: 92%
“…2c), like that of Lake Superior, inhabited deeper water than the lean, and was fatter than the lean as evidenced by its lower percentage buoyancy. The high fat levels in Lake Superior siscowets are hypothesized to be an adaptation for reducing the energetic cost of extensive vertical migration (Henderson and Anderson 2002;Hrabik et al 2006;Jensen et al 2006). A siscowet-like, fat (low percent buoyancy) lake charr was not observed by the author during field surveys of the McTavish (northeast) arm of Great Bear Lake during 2004.…”
Section: Background On Formsmentioning
confidence: 92%
“…This has been suggested as a strategy to increase bioenergetic efficiency, where fish capitalize on the differences in temperature between deep and shallow waters and choose depths so as to maximize their growth rate (e.g., Neverman and Wurtsbaugh 1994). However, it has also been suggested that DVM is driven by a habitat specific trade-off between predation risk and feeding opportunities (e.g., Scheuerell and Schindler 2003;Hrabik et al 2006), similar to the argument for seasonal migration discussed above. Prey fish should thus migrate to the dark, deeper layers during daytime to avoid predation by visually oriented piscivores and then return to the shallow depths during night to feed on zooplankton.…”
Section: Diel Migrationsmentioning
confidence: 99%
“…Hrabik et al 2006. Sprat in the area sampled in the present study also performed DVMs in the feeding season and were distributed in the upper part of the water column at night, where a secondary thermocline at this time of year provided high temperatures above the halocline (Cardinale et al 2003).…”
Section: Discussionmentioning
confidence: 86%